MORFOMETRIK CANGKANG FAMILI TROCHIDAE PADA PADANG LAMUN DI PERAIRAN TELUK BALIKPAPAN - Hidayat, Syaril; Irawan, Aditya; Sari, Lily Inderia (Jurnal Tropical Aquatic Sciences, 2023)
This study aims to determine the morphometrics of the Trochidae family in seagrass beds in Balikpapan Bay, East Kalimantan. This research was conducted from October 2022 to January 2023. Data was collected using quadrant transect sampling. Data analysis used to determine the morphometrics of the Trochidae family in seagrass beds is length and width of shell, abundance, diversity index (H'), uniformity index (E), and dominance index (D). Sampling was carried out using a quadrant transect measuring 0.5 x 0.5 m2 at 4 stations with 3 repetitions at each station. Two species of seagrass were found, namely E. acoroides and T. hemprichii. Two species were found from the Trochidae family, namely U. costatum and U. vestarium. The highest abundance of the Trochidae family was the species U. costatum with 288 individuals/m2 while the abundance of the Trochidae family U.vestarium was 120 individuals/m2. Based on the results of measuring the length of the shell, it was found that the shell length of U.costatum ranged from 1.0 cm – 1.5 cm with an average of 1.3 cm and U.vestarium ranged from 0.4 cm – 1.2 cm with an average of 0.9 cm. Measurement of the width of the shell found that the shell width of U.costatum ranged from 1.2 cm – 1.7 cm with an average of 1.5 cm and U. vestarium ranged from 0.4 cm – 1.3 cm with an average of 1.0 cm. Based on the research results, the ratio of the length and width of the total shell of U. costatum species was 1 : 1.2 and U. vestarium 1 : 1.1. The Diversity Index (H') of the Trochidae family in the waters of Balikpapan Bay, with an average value of 0.54, is in the low diversity category. The Uniformity Index (E) of the Trochidae family from the four stations, with an average value of 0.78, is in the High uniformity category. The Dominance Index (D) of the Trochidae family from the four stations, with an average value of 0.61, is in the Moderate Dominance category.